Tesouros de arte - Rosie, Dickins (Pepin Pr; India, 1763)
This book contains stunning images for use as a graphic resource, or inspiration. All the illustrations are stored in high-resolution format on the enclosed free CD-ROM and are ready to use for professional quality printed media and web page design. The pictures can also be used to produce postcards, or to decorate your letters, flyers, etc. They can be imported directly from the CD into most design, image-manipulation, illustration, word-processing and e-mail programs; no installation is required. For most applications, single images can be used free of charge. Please consult the introduction to this book, or visit our website for conditions.